Nature in corrosion–erosion surface for [TiN/TiAlN]n nanometric multilayers growth on AISI 1045 steel (2012)
The aim of this work is to characterize the electrochemical behavior of [TiN/TiAlN]n multilayer coatings under corrosion–erosion condition. The multilayers with bilayer numbers (n) of 2, 6, 12, and 24 and/or bilayer period (Λ) of 1500 nm, 500 nm, 250 nm, 150 nm and 125 nm were deposited by magnetron sputtering technique on Si (100) and AISI 1045 steel substrates. Both, the TiN and the TiAlN structures for multilayer coatings were evaluated via X-ray diffraction analysis. Mechanical and tribological properties were evaluated via nanoindentation measurements and scratch test respectively. Silica particles were used as abrasive material on corrosion–erosion test in 0.5 M of H2SO4 solution at impact angles of 30° and 90° over surface. The electrochemical characterization was carried out using polarization resistance technique (Tafel), in order to observe changes in corrosion rate as a function of the bilayer number (n) or the bilayer period (Λ) and the impact angle. Corrosion rate values of 9115 μm y for uncoated steel substrate and 2615 μm y for substrate coated with n = 24 (Λ = 125 nm) under an impact angle of 30° were found. On the other hand, for an impact angle of 90° the corrosion rate exhibited 16401 μm y for uncoated steel substrate and 5331 μm y for substrate coated with n = 24 (Λ = 125 nm). This behavior was correlated with the curves of mass loss for both coated samples and the surface damage was analyzed via scanning electron microscopy images for the two different impact angles. These results indicate that TiN/TiAlN multilayer coatings deposited on AISI 1045 steel represent a practical solution for applications in corrosive–erosive environments